Estudo da fragilidade sísmica de pórticos de concreto armado com irregularidades estruturais - Pereira, Eduardo Marques Vieira, 1994- (2021)
Orientadores: Gustavo Henrique Siqueira, Luiz Carlos Marcos Vieira Júnior